Multi-robot formation control using distance and orientation. (17th July 2016) - Lopez-Gonzalez, A.; Ferreira, E. D.; Hernandez-Martinez, E. G.; Flores-Godoy, J. J.; Fernandez-Anaya, G.; Paniagua-Contro, P.
Abstract : Formation control analyses the convergence of a group of mobile agents to predefined geometric patterns. In traditional approaches, it is assumed that each agent knows the exact position of certain members of the group with respect to a reference frame and the associated control laws are designed according to inter-robot relative positions. Designing a more decentralized scheme, this paper proposes a formation scheme, using Lyapunov techniques, considering that the local controllers of the agents can be equipped with distance and orientation sensors. The main result of the paper applies to certain distance-based potential functions with inter-robot collision avoidance and an arbitrary undirected formation graph. Also, the control law includes an integral-type control that eliminates the effects of the dead-zone of actuators in order to avoid the standard techniques of normalization. The control approach is analyzed for omnidirectional robots with numerical simulations and extended for unicycle-type robots with real-time experiments. Graphical Abstract: